Improving Cassava Productivity by Soil Bioaugmentation with Phosphate-Solubilizing Actinomycetes and Fungi - Alimuddin Ali; Muhammad Juanda; A. Farchan Sjahid; Herlina Rante (Jurnal AgroBiogen, 2020)
Cassava is one of the most important food commodities, but its cultivation technique must be improved, especially the technology in increasing soil fertility. Lack of phosphate (P), one of the major biological nutrients in soil, can reduce agricultural production. Some P-solubilizing microbes can play an important role in increasing the availability of P for plants. The purpose of this study was to evaluate the ability of P-solubilizing microbes isolated from cassava rhizosphere in improving the growth of cassava after soil bioaugmentation with the formula of selected microbes. A total of 50 isolates were successfully isolated from cassava plant rhizosphere collected from several locations in South Sulawesi. In vitro screening on Pikovskaya agar media resulted in six Actinomycetes and six fungal isolates with the best P hydrolysis capacity. One Actinomycetes isolate (Streptomyces sp. A-SDR01) and one fungal isolate (Penicillium sp. F-SKG17) with nonantagonistic effect to each other based on in vitro test were able to improve the vegetative growth of cassava under in planta test. Combination of both isolates in a gum arabic formulation increased plant height and productivity compared to untreated plants when applied as soil bioaugmentation in limited field trials at four locations in South Sulawesi. Therefore, application of P-solubilizing microbes that possess soil bioaugmentation properties is recommended for increasing the growth of cassava plants and their use as microbial biofertilizers should be extended to wider areas.